Говийн малчдын зудны эрсдлийн тухай санал: малчид болон засгийн газар хоёулаа хариуцлагатай байх ёстой - Анника Эриксэн (Politology, 2023)
This paper interrogates discourses critiquing Mongolian herders’ "laziness" and "irresponsibility" in relation to winter risk. Twenty years after the transition from socialism to capitalism, many international development professionals and urban Mongolians feel that herders have been spoiled by state assistance. This paper challenges argues that herders take responsibility for their own herds to the extent possible given the current climate and availability of resources. It outlines several of herders’ strategies for mitigating the risk of zud disasters and discusses herders’ views on issues of risk and responsibility. While it is true that most herders still expect state support during severe winters, they perceive the support as a necessary complement to, rather than as a substitute for, rigorous individual efforts to manage risk. While "slackers" exist in every sphere of society, most herders that participated in the research place as much emphasis on individual responsibility as their critics.